An Anomalous Configuration of Coronary Artery: A Cadaveric Study - Rajani Singh (Case Reports in Cardiology)
Anatomical variations in relation to coronary artery and its branches will help cardiac surgeons for refining imaging techniques and coronary artery bypass grafting. A heart was detected with multiple anomalies of coronary arteries in a cadaver. The anomalies of coronary arteries in terms of origin, number of ostia, courses, and presence of myocardial bridges were described, and related clinical implications were highlighted in the present study. The knowledge of variant anatomy may be of paramount importance to anatomists for variant anatomy and to cardiac surgeon for proper diagnosis and treatment of cardiac ailments including radiologists to refine image interpretation.